Konstruksi dan Analisis Hukum Islam Terhadap Proses Ta’aruf Menuju Pernikahan Melalui Media Sosial di Kalangan Gen-Z - Munawarsyah; Nurlinda Yani (Ameena Journal, 2026)
Generation Z, who have grown up in the digital era, face complex challenges in finding a life partner without becoming involved in dating practices that may contradict religious norms. Therefore, this study aims to examine in depth the construction of the ta’aruf process leading to marriage through social media among Gen-Z, analyze its impacts, and review it from the perspective of Islamic law. This research employs a qualitative approach using normative legal research through a library research method. The data were analyzed using content analysis and critical analysis techniques. The findings reveal that the construction of digital ta’aruf operates systematically through three stages: (1) identity initiation and curation through the exchange of Curriculum Vitae (CV) facilitated by an administrator; (2) virtual mediation through third-party communication groups to prevent virtual khalwah, followed by a face-to-face meeting (nadzor); and (3) the formalization of commitment through khitbah involving both families. The positive impacts include time efficiency, broader networking opportunities, and the provision of a Sharia-compliant alternative for partner selection, while the negative impacts involve the risks of profile manipulation (catfishing) and privacy violations. From the perspective of Islamic law, digital ta’aruf is considered permissible as a means (wasilah) that aligns with the principles of Maqāṣid al-Sharī‘ah, provided that it is free from deception (tadlīs), facilitated by a mediator, and involves the direct participation of a guardian (wali).